Expression profile of circRNA in peripheral blood mononuclear cells of patients with rheumatoid arthritis - Huangxin Lu; Yifan Yang; Dong Kuang; Ping Liu; Junping Yang (BMC Medical Genomics, 2022)
Abstract Background Circular RNAs (circRNAs) is a newly discovered non-coding RNA that can be used as biomarkers in clinical blood samples. This study aims to screen differentially expressed circular RNAs in PBMCs of patients with rheumatoid arthritis (RA) to determine new biomarkers for the diagnosis of RA. Methods The differentially expressed circRNAs in peripheral blood mononuclear cells (PBMCs) of 4 RA patients and 4 healthy participants were screened and analyzed by gene microarray technology. We then validated some of the differentially expressed circRNAs in PBMCs of 20 RA patients, 10 systemic lupus erythematosus (SLE) patients and 20 healthy participants using reverse transcription-quantitative polymerase chain reaction amplification (RT-qPCR). Spearman correlation test was performed to analyze the correlation between differentially expressed circRNAs and clinical variables in RA patients. Receiver operating characteristic (ROC) curves were calculated to evaluate the diagnostic value of circRNAs. Results Differential analysis obtained 149 circRNAs with significant up-regulated expression and 250 circRNAs with significant down-regulated expression, which predicted the miRNA targets and binding sites. Compared with SLE and health control group, hsa_circ_101328 was found to be a common gene with differential expression of RA. Besides, correlation analysis revealed significant correlation between hsa_circ_101328 and positive CRP. ROC curve analysis showed that hsa_circ_101328 has the potential of RA diagnosis. Conclusion We identified some dysregulated circRNAs in PBMCs from RA patients, and hsa_circ_101328 may be a novel and effective biomarker for early diagnosis of RA.